Dolostones from the Louisiade Plateau and Norfolk Ridge - N. Mortimer; K. Faure; F. Hauff; D. Strogen; B. Pelletier (Australian Journal of Earth Sciences, 2026)

A VNIR spectral database of terrestrial magmatic rocks for the interpretation of Martian plagioclase hyperspectral detections - M. Barthez; J. Flahaut; M. Guitreau; R. Pik; G. Ito; C. Delangle; J.-P. Gremilliet; B. Luais; F. Faure (Icarus, 2026)

A reappraisal of the amorphization kinetics of water ice: Combined experimental and numerical investigations and amorphization cross-sections in the 90–120 K range - A. Moingeon; E. Quirico; O. Poch; M. Faure; P. Boduch; A. Domaracka; H. Rothard; B. Schmitt; M. Toulemonde; J. Rangama; D. Bockelée-Morvan; T. Fouchet; et al. (Icarus, 2026)

Structural controls on simultaneous earthquake clustering and normal fault synchronization - F. Iezzi; C. Sgambato; G. Roberts; Z. Mildon; J. Robertson; J. Faure Walker; I. Papanikolaou; A.M. Michetti; S. Mitchell; R. Shanks; R. Phillips; K.J.W. McCaffrey; et al. (Earth and Planetary Science Letters, 2025)

Determination of free and derivative terpenoids and sterols in spent coffee grounds by two-dimensional liquid chromatography - supercritical fluid chromatography coupled to high-resolution mass spectrometry - Irene Caño-Carrillo; Magali Batteau; Lauriane Bruna; Bienvenida Gilbert-López; Juan F. García-Reyes; Gregory Chatel; Karine Faure (Food Chemistry, 2025)

Characteristics and modelling of slip-rate variability and temporal earthquake clustering across a distributed network of active normal faults constrained by in situ 36Cl cosmogenic dating of fault scarp exhumation, central Italy - G.P. Roberts; F. Iezzi; C. Sgambato; J. Robertson; J. Beck; Z.K. Mildon; I. Papanikolaou; A.M. Michetti; J.P. Faure Walker; S. Mitchell; M. Meschis; R. Shanks; et al. (Journal of Structural Geology, 2025)

Ecosystem based approach to assess the impact of invasive or expanding species in the lower Saône River - T. Changeux; A. Dragotta; E. Franquet; N. Stolzenberg; J.F. Fruget; L. Marion; C. Souty-Grosset; O. Anneville; L. Cavalli; J.P. Faure; N. Corget; F. Josserand; et al. (Anthropocene, 2024)

Spatial migration of temporal earthquake clusters driven by the transfer of differential stress between neighbouring fault/shear-zone structures - G.P. Roberts; C. Sgambato; Z.K. Mildon; F. Iezzi; J. Beck; J. Robertson; I. Papanikolaou; A.M. Michetti; J.P. Faure Walker; M. Meschis; R. Shanks; R. Phillips; et al. (Journal of Structural Geology, 2024)

The distribution of coastal fish eDNA sequences in the Anthropocene - Laetitia Mathon; Virginie Marques; Stéphanie Manel; Camille Albouy; Marco Andrello; Emilie Boulanger; Julie Deter; Régis Hocdé; Fabien Leprieur; Tom B. Letessier; Nicolas Loiseau; Eva Maire; et al. (Global Ecology and Biogeography, 2023)
Aim Coastal fishes have a fundamental role in marine ecosystem functioning and contributions to people, but face increasing threats due to climate change, habitat degradation and overexploitation. The extent to which human pressures are impacting coastal fish biodiversity in comparison with geographic and environmental factors at large spatial scale is still under scrutiny. Here, we took advantage of environmental DNA (eDNA) metabarcoding to investigate the relationship between fish biodiversity, including taxonomic and genetic components, and environmental but also socio‐economic factors. Location Tropical, temperate and polar coastal areas. Time period Present day. Major taxa studied Marine fishes. Methods We analysed fish eDNA in 263 stations (samples) in 68 sites distributed across polar, temperate and tropical regions. We modelled the effect of environmental, geographic and socio‐economic factors on α‐ and β‐diversity. We then computed the partial effect of each factor on several fish biodiversity components using taxonomic molecular units (MOTU) and genetic sequences. We also investigated the relationship between fish genetic α‐ and β‐diversity measured from our barcodes, and phylogenetic but also functional diversity. Results We show that fish eDNA MOTU and sequence α‐ and β‐diversity have the strongest correlation with environmental factors on coastal ecosystems worldwide. However, our models also reveal a negative correlation between biodiversity and human dependence on marine ecosystems. In areas with high dependence, diversity of all fish, cryptobenthic fish and large fish MOTUs declined steeply. Finally, we show that a sequence diversity index, accounting for genetic distance between pairs of MOTUs, within and between communities, is a reliable proxy of phylogenetic and functional diversity. Main conclusions Together, our results demonstrate that short eDNA sequences can be used to assess climate and direct human impacts on marine biodiversity at large scale in the Anthropocene and can further be extended to investigate biodiversity in its phylogenetic and functional dimensions.

A ring trial to harmonize Toxoplasma gondii microsatellite typing: comparative analysis of results and recommendations for optimization - M. Joeres; G. Cardron; K. Passebosc-Faure; N. Plault; M. Fernández-Escobar; C. M. Hamilton; L. O’Brien-Anderson; R. Calero-Bernal; L. Galal; C. Luttermann; P. Maksimov; F. J. Conraths; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)
A ring trial among five European laboratories was organized to reach consistency in microsatellite (MS) typing of the zoonotic parasite Toxoplasma gondii . Three sample sets were circulated and analyzed by each laboratory following a previously published method that is based on fragment length polymorphism of 15 MS markers. The first sample set compared typing results in general and focused on effects of DNA concentration; the second sample set focused on the polymorphic fingerprinting markers that can differentiate T. gondii strains within the same archetypal lineage; and the third set focused on non-archetypal genotypes. Methodological variations between laboratories, including the software programs used to determine MS fragment length, were collated using a questionnaire. Overall, lineage-level typing results reached a high level of agreement, especially in samples with the highest DNA concentrations. However, laboratory-specific differences were observed for particular markers. Major median differences in fragment length, of up to 6 base pairs, were related to the fluorophore used to label fragment-specific primers. In addition, primer pairs with identical sequences obtained from different suppliers resulted in fragments of differing length. Furthermore, differences in the way the sequencing profiles were assessed and interpreted may have led to deviating results in fragment length determination. Harmonization of MS typing, for example, by using the same fluorophores or by numerical adjustments applied to the fragment-lengths determined, could improve the uniformity of the results across laboratories. This is the first interlaboratory comparison, providing guidelines (added as a supplement) for the optimization of this technique.

On a radiolytic origin of red organics at the surface of the Arrokoth Trans-Neptunian Object - Eric Quirico; Aurore Bacmann; Cédric Wolters; Basile Augé; Laurène Flandinet; Thibault Launois; John F. Cooper; Véronique Vuitton; Thomas Gautier; Lora Jovanovic; Philippe Boduch; Hermann Rothard; et al. (Icarus, 2023)

Origin of nitrogen on Mars: First in situ N isotope analyses of martian meteorites - C. Deligny; E. Füri; E. Deloule; A.H. Peslier; F. Faure; Y. Marrocchi (Geochimica et Cosmochimica Acta, 2023)

Interpreting biomonitoring data: Introducing the international human biomonitoring (i-HBM) working group's health-based guidance value (HB2GV) dashboard - Shoji F. Nakayama; Annie St-Amand; Tyler Pollock; Petra Apel; Yu Ait Bamai; Dana Boyd Barr; Jos Bessems; Antonia M. Calafat; Argelia Castaño; Adrian Covaci; Radu Corneliu Duca; Sarah Faure; et al. (International Journal of Hygiene and Environmental Health, 2023)

Identification of two novel putative satellite RNAs with hammerhead structures in the virome of French and Spanish carrot samples - B. M. Babalola; D. Schönegger; C. Faure; A. Marais; A. Fraile; F. Garcia-Arenal; T. Candresse (Archives of Virology, 2022)

Phylogeography in continuous space: coupling species distribution models and circuit theory to assess the effect of contiguous migration at different climatic periods on genetic differentiation in B usseola fusca ( L epidoptera: N octuidae) - S. Dupas; B. le Ru; A. Branca; N. Faure; G. Gigot; P. Campagne; M. Sezonlin; R. Ndemah; G. Ong'amo; P.‐A. Calatayud; J.‐F. Silvain (Molecular Ecology, 2014)
Current population genetic models fail to cope with genetic differentiation for species with large, contiguous and heterogeneous distribution. We show that in such a case, genetic differentiation can be predicted at equilibrium by circuit theory, where conductance corresponds to abundance in species distribution models ( SDM s). Circuit‐ SDM approach was used for the phylogeographic study of the lepidopteran cereal stemborer B usseola fusca F üller ( N octuidae) across sub‐ S aharan A frica. Species abundance was surveyed across its distribution range. SDM s were optimized and selected by cross‐validation. Relationship between observed matrices of genetic differentiation between individuals, and between matrices of resistance distance was assessed through Mantel tests and redundancy discriminant analyses ( RDA s). A total of 628 individuals from 130 localities in 17 countries were genotyped at seven microsatellite loci. Six population clusters were found based on a B ayesian analysis. The eastern margin of D ahomey gap between E ast and W est A frica was the main factor of genetic differentiation. The SDM projections at present, last interglacial and last glacial maximum periods were used for the estimation of circuit resistance between locations of genotyped individuals. For all periods of time, when using either all individuals or only E ast A frican individuals, partial M antel r and RDA conditioning on geographic distance were found significant. Under future projections (year 2080), partial r and RDA significance were different. From this study, it is concluded that analytical solutions provided by circuit theory are useful for the evolutionary management of populations and for phylogeographic analysis when coalescence times are not accessible by approximate B ayesian simulations.

Factors associated with recurrence of catheter-related bloodstream infections in home parenteral nutrition patients - G. Béraud; D. Seguy; S. Alfandari; X. Lenne; F. Leburgue; K. Faure; B. Guery (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Genome-wide association analysis to identify chromosomal regions determining components of earliness in wheat - J. Le Gouis; J. Bordes; C. Ravel; E. Heumez; S. Faure; S. Praud; N. Galic; C. Remoué; F. Balfourier; V. Allard; M. Rousset (Theoretical and Applied Genetics, 2012)

Crystallochemistry and origin of pyroxenes in komatiites - Sebastien Bouquain; N. T. Arndt; E. Hellebrand; F. Faure (Contributions to Mineralogy and Petrology, 2009)

Land use monitoring by remote sensing in tropical forest areas in support of the Kyoto Protocol: the case of French Guiana - N. Stach; A. Salvado; M. Petit; J. F. Faure; L. Durieux; C. Corbane; P. Joubert; D. Lasselin; M. Deshayes (International Journal of Remote Sensing, 2009)

Comparative phylogeography among hydrothermal vent species along the East Pacific Rise reveals vicariant processes and population expansion in the South - S. PLOUVIEZ; T. M. SHANK; B. FAURE; C. DAGUIN‐THIEBAUT; F. VIARD; F. H. LALLIER; D. JOLLIVET (Molecular Ecology, 2009)
The use of sequence polymorphism from individual mitochondrial genes to infer past demography has recently proved controversial because of the recurrence of selective sweeps acting over genes and the need for unlinked multilocus data sets. However, comparative analyses using several species for one gene and/or multiple genes for one species can serve as a test for potential selective effects and clarify our understanding of historical demographic effects. This study compares nucleotide polymorphisms in mitochondrial cytochrome oxidase I across seven deep‐sea hydrothermal vent species that live along the volcanically active East Pacific Rise. Approximate Bayesian Computation (ABC) method, developed to trace shared vicariant events across species pairs, indicates the occurrence of two across species divergence times, and suggests that the present geographical patterns of genetic differentiation may be explained by two periods of significant population isolation. The oldest period dates back 11.6 Ma and is associated with the vent limpet Lepetodrilus elevatus , while the most recent period of isolation is 1.3 Ma, which apparently affected all species examined and coincides with a transition zone across the equator. Moreover, significant negative Tajima’s D and star‐like networks were observed for all southern lineages, suggesting that these lineages experienced a concomitant demographic and geographical expansion about 100 000–300 000 generations ago. This expansion may have initiated from a wave of range expansions during the secondary colonization of new sites along the Southern East Pacific Rise (founder effects below the equator) or recurrent bottleneck events because of the increase of eruptive phases associated with the higher spreading rates of the ridge in this region.

The Flow of Antimicrobial Peptide Genes Through a Genetic Barrier Between Mytilus edulis and M. galloprovincialis - Eva Boon; Matthieu F. Faure; Nicolas Bierne (Journal of Molecular Evolution, 2009)

Incidence of kyphosis deformities in natural population of Atherina lagunae (Trabelsi et al. 2002) from the Tunis North Lake, Tunisia - N. Ayed; E. Faure; J.-P. Quignard; F. Maamouri; M. Trabelsi (Marine Biology, 2008)

Phylogeography and population genetics of the maize stalk borer Busseola fusca (Lepidoptera, Noctuidae) in sub‐Saharan Africa - M. SEZONLIN; S. DUPAS; B. LE RÜ; P. LE GALL; P. MOYAL; P.‐A. CALATAYUD; I. GIFFARD; N. FAURE; J.‐F. SILVAIN (Molecular Ecology, 2006)
The population genetics and phylogeography of African phytophagous insects have received little attention. Some, such as the maize stalk borer Busseola fusca , display significant geographic differences in ecological preferences that may be congruent with patterns of molecular variation. To test this, we collected 307 individuals of this species from maize and cultivated sorghum at 52 localities in West, Central and East Africa during the growing season. For all collected individuals, we sequenced a fragment of the mitochondrial cytochrome b . We tested hypotheses concerning the history and demographic structure of this species. Phylogenetic analyses and nested clade phylogeographic analyses (NCPA) separated the populations into three mitochondrial clades, one from West Africa, and two — Kenya I and Kenya II — from East and Central Africa. The similar nucleotide divergence between clades and nucleotide diversity within clades suggest that they became isolated at about the same time in three different refuges in sub‐Saharan Africa and have similar demographic histories. The results of mismatch distribution analyses were consistent with the demographic expansion of these clades. Analysis of molecular variance ( amova ) indicated a high level of geographic differentiation at different hierarchical levels. NCPA suggested that the observed distribution of haplotypes at several hierarchical levels within the three major clades is best accounted for by restricted gene flow with isolation by distance. The domestication of sorghum and the introduction of maize in Africa had no visible effect on the geographic patterns observed in the B . fusca mitochondrial genome.

Parallels in the evolution of the two largest New and Old World seed‐beetle genera (Coleoptera, Bruchidae) - G. J. KERGOAT; N. ALVAREZ; M. HOSSAERT‐MCKEY; N. FAURE; J.‐F. SILVAIN (Molecular Ecology, 2005)
This study provides the first phylogenetic analysis of a large sample of the two largest genera of seed‐beetles, Acanthoscelides Schilsky and Bruchidius Schilsky, which mostly feed on legumes (Fabaceae). The goal of this study was to investigate evolutionary patterns in relation to biogeography and host‐plant associations. We used three mitochondrial molecular markers and parsimony and Bayesian inference methods to reconstruct the phylogeny of 76 species. In addition, we critically reviewed host‐plant records in the literature for these two bruchid genera. Our results demonstrated the existence of two major clades, one New World and one largely Old World, which generally correspond to the two genera. Yet, current classification of several species is erroneous, so that both genera as currently defined are paraphyletic. We highlighted a strong trend toward specialization (with high taxonomic conservatism in host‐plant use) exhibited by the two studied genera. However, we showed the existence of several host shifts during the evolution of this group of bruchids. Our phylogenetic hypotheses and our evaluation of host‐plant associations both suggest that the two genera have undergone parallel evolution, as they have independently colonized similar host plants in their respective areas of distribution. Our estimation of divergence times indicated a more ancient origin for bruchids than that suggested by the fossil records. Interestingly, the suggested timing of diversification is consistent with the hypothesis of a radiation that could have occurred contemporaneously with the diversification of their legume hosts.

Effect of Wetting on the Dynamics of Drainage in Porous Media - N. Shahidzadeh-Bonn; A. Tournié; S. Bichon; P. Vié; S. Rodts; P. Faure; F. Bertrand; A. Azouni (Transport in Porous Media, 2004)

Occurrence of partial hybrids in wide crosses between sunflower (Helianthus annuus) and perennial species H. mollis and H. orgyalis - N. Faure; H. Serieys; A. Bervillé; E. Cazaux; F. Kaan (Theoretical and Applied Genetics, 2002)

Partial hybridization in crosses between cultivated sunflower and the perennial Helianthus mollis: effect of in vitro culture compared to natural crosses - N. Faure; H. Serieys; F. Kaan; A. Bervillé (Plant Cell Reports, 2002)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

A simple and efficient method for in vitro shoot regeneration from leaves of lavandin ( Lavandula ×× intermedia Emeric ex Loiseleur) - S. Dronne; F. Jullien; J.-C. Caissard; O. Faure (Plant Cell Reports, 1999)

Mannitol and thidiazuron improve in vitro shoot regeneration from spearmint and peppermint leaf disks - O. Faure; F. Diemer; S. Moja; F. Jullien (Plant Cell, Tissue and Organ Culture (PCTOC), 1998)

Holocene sea level changes and reef development in the southwestern Indian Ocean - G. F. Camoin; M. Colonna; L. F. Montaggioni; J. Casanova; G. Faure; B. A. Thomassin (Coral Reefs, 1997)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)